Characterization, thermal and antimicrobial properties of hybrid cellulose nanocomposite films with in-situ generated copper nanoparticles in tamarindus indica nut powder - Muthu Kumar, T. Senthil; Chandrasekar, M.; Senthilkumar, K.; Ilyas, R. A.; Salit, Mohd Sapuan; Hariram, N.; Rajulu, A. Varada; Rajini, N.; Siengchin, Suchart (Springer, 2021)
Hybrid cellulose nanocomposite films (HCNFs) were fabricated using cellulose from cotton linters as the matrix, and varying loadings (5 to 25wt.%) of modified tamarind nut power (TNP) with in situ generated copper nanoparticles as the reinforcing fillers. These hybrid composite films were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), and antibacterial tests. The inclusion of modified tamarind nut powder improved the crystallinity of the hybrid nanocomposites by 13%. From the FTIR analysis, it could be ascertained that there was no notable change in the chemical composition of the matrix with the amendment of the filler. Further, the shift in peak intensity with increasing concentration of the filler shows the formation of hydrogen bond between the filler and the matrix. The TGA analysis revealed that the degradation temperature of hybrid nanocomposites increased until HCNFs with 15wt.% modified tamarind nut powder. The hybrid nanocomposites exhibited better antibacterial properties against all the pathogens used in the study. These hybrid nanocomposites were found to have superior antibacterial activity, thermal resistance, and improvement in crystallinity. Thus, these bio-based materials can be used to replace the existing packaging materials in the food packaging and help to reduce the impact of conventional plastics on the environment.